The Result of Taking Mare’s Milk for Nonalcoholic Steatohepatitis - Bakytzhan Bimbetov (Journal of Global Pharma Technology, 2019)
Nonalcoholic steatohepatitis (NASH) is a severe form of nonalcoholic fatty liver disease (NAFLD) and is linked to overweight, obesity and metabolic syndrome. The main role in treating NAFLD is attributed to leading a healthy lifestyle, keeping a healthy low-calorie diet and high physical activity. In dealing with issues of healthy diets of patients with NASH, mare’s milk can be considered a pathogenically based, highly effective and affordable natural therapeutic dietary agent. The value of the product is defined by its similarity to the chemical components of women’s breast milk. This article reports a case of a successful treatment of NASH with the help of monotherapy using sublimated mare’s milk within a relatively short period of time, devoid of laborious dieting, physical activity or any side effects.Keywords: Non-alcoholic fatty liver diseases, Non-alcoholic steatohepatitis, Mare's milk, Sublimated mare's milk, Medical and dietary properties of mare's milk.